Histopathological features of organs in a rat model of mammary carcinogenesis: a reference database - Helena, Vala (2021)
Mammary tumors’ development was induced through the intraperioneal administration of the carcinogen N-methyl-N-nitrosourea (MNU). Animals from group control were injected with the vehicle (saline solution). Animals were sacrificed at 25 weeks-old and the organs were histopathologically evaluated. A higher number of lesions was observed in the organs of animals from group MNU. The animals from group control did not present any lesion in lymph nodes. Independently of the experimental group, the internal organs presented hemodynamic alterations, degenerative and inflammatory changes. Hemodynamic changes may be consequence of euthanasia method. As expected, the higher number and the higher grade of the lesions in group MNU were due to the carcinogen administration.